2015
DOI: 10.1159/000431288
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Calcification Progression Is an Independent Predictor of Mortality in Patients on Haemodialysis

Abstract: Background: We previously reported that vascular calcification (VC) score was associated with mortality in patients on haemodialysis (HD) and that a high serum level of parathyroid hormone (PTH) and fibroblast growth factor (FGF)-23 were the only factors associated with VC progression. Aim: To assess the impact of VC progression on HD patient survival. Methods: The study cohort including 85 HD patients studied between 2006 and 2007 and between 2009 and 2010 was divided into patients with VC progression (PG+, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…This type of calcification results in the increase in systolic and decrease in diastolic blood pressure, followed by an increase in the afterload and hypertrophy of the left ventricle and the reduction of coronary blood flow in diastole. 55 These changes are associated with increased cardiovascular risk. 56 The main factor stimulating transformation of vascular smooth muscle cells (VSMC) to osteoblast-like cells is hyperphosphatemia.…”
Section: Sclerostin In Chronic Kidney Diseasementioning
confidence: 99%
“…This type of calcification results in the increase in systolic and decrease in diastolic blood pressure, followed by an increase in the afterload and hypertrophy of the left ventricle and the reduction of coronary blood flow in diastole. 55 These changes are associated with increased cardiovascular risk. 56 The main factor stimulating transformation of vascular smooth muscle cells (VSMC) to osteoblast-like cells is hyperphosphatemia.…”
Section: Sclerostin In Chronic Kidney Diseasementioning
confidence: 99%
“…In addition, myocardial fibrosis and arrhythmia may develop because of tissue calcification. The presence of VC increases mortality …”
Section: General Considerations On Vascular Calcificationmentioning
confidence: 99%
“…The results of our research are in concordance with these results. Some studies demonstrated that VC can predict the CDV mortality risk in non-renal population [ 27 , 29 ], but, especially in patients with renal failure on HD treatment [ 30 , 31 ] and on PD [ 11 , 12 ]. Several studies demonstrated that VC represent a link between renal and CDV diseases [ 17 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%